2009
DOI: 10.1038/nrc2693
|View full text |Cite
|
Sign up to set email alerts
|

When mutants gain new powers: news from the mutant p53 field

Abstract: Ample data indicate that mutant p53 proteins not only lose their tumour suppressive functions, but also gain new abilities that promote tumorigenesis. Moreover, recent studies have modified our view of mutant p53 proteins, portraying them not as inert mutants, but rather as regulated proteins that influence the cancer cell transcriptome and phenotype. This influence is clinically manifested as association of TP53 mutations with poor prognosis and drug resistance in a growing array of malignancies. Here, we rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
1,076
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,017 publications
(1,107 citation statements)
references
References 177 publications
22
1,076
1
8
Order By: Relevance
“…Mutant p53 and miR-155 expression are both associated with invasive properties in vivo (2,10), which prompted us to investigate whether they promote malignant transformation through a similar oncogenic axis. We initially determined if miR-155 can phenocopy mutant p53 in its ability to drive invasion and mensenchymal transformation when expressed in the same genetic background.…”
Section: Mir-155 Is a Target Microrna Of Mutant P53mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant p53 and miR-155 expression are both associated with invasive properties in vivo (2,10), which prompted us to investigate whether they promote malignant transformation through a similar oncogenic axis. We initially determined if miR-155 can phenocopy mutant p53 in its ability to drive invasion and mensenchymal transformation when expressed in the same genetic background.…”
Section: Mir-155 Is a Target Microrna Of Mutant P53mentioning
confidence: 99%
“…However, inactivation of the tumor suppressor function of p53 is not the only outcome of a TP53 mutation. Increasing evidence suggests that the mutated p53 protein exhibits traits consistent with the acquisition of an oncogenic gain-of-function (1,2). For example, mutations of TP53 gene are frequently missense, involve similar codons within the p53 DNA binding domain and are expressed at remarkably high levels in tumor cells (1).…”
Section: Introductionmentioning
confidence: 99%
“…Two apparently contradictory results blur our vision as to the role of p53 in skin cancer: mice deficient for TP53 develop tumors resembling SCC after UV irradiation (Ziegler et al, 1994;Li et al, 1998;Jiang et al, 1999), whereas Li-Fraumeni syndrome patients, who have a germline mutation in TP53, are not reported to be at increased risk for SCC (Malkin et al, 1990). These findings should be put in the perspective of the growing body of evidence showing that p53 missense mutants not only lose normal p53 functions, but are also often pro-active in tumor formation (reviewed by Donzelli et al, 2008;Brosh and Rotter, 2009). Indeed, a set of gain-of-function mechanisms resulting from p53 mutations have been documented.…”
Section: Activation Of Klf4 By Mutant P53mentioning
confidence: 99%
“…RD cells carry a homozygous p53 Arg248Trp mutation, 29,30 which renders the protein defective in DNA binding. 3 Wild-type p53 function was restored in RD cells by expressing a tamoxifen-inducible p53-estrogen receptor (ER) fusion (Figure 1a). By tuning the translation level 31 of the p53-ER ( Supplementary Figures 1 and 2a-c), we showed that restoration of wild-type p53 over a range of expression levels did not result in apoptotic and/or necrotic cells 32 in RD cells (Supplementary Figures 2d-g).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Among the diverse functions attributed to p53, a growing body of evidence supports its role in regulation of differentiation and maintenance of cellular function and integrity. 1,[4][5][6][7] For example, p53 represses Nanog to maintain genetic stability of the stem cell pool by promoting differentiation of mouse embryonic stem cells (mESCs) after DNA damage.…”
mentioning
confidence: 99%